Coastal wetlands of the world : Geology, ecology, distribution and applications - Scott, David B.; Frail-Gauthier, Jennifer; Mudie, Petra J. (Cambridge : Cambridge University Press, 2014)
Salt marshes and mangrove forests, the intertidal wetlands of the world's coastlines, provide key ecological services to all areas of the globe. This cutting-edge, richly illustrated book introduces the essential elements of coastal wetlands and their applications. The book opens by introducing coastal oceanography, the physical features of wetlands, their .ecology, and human impacts upon them, giving all students the necessary background for wetlands studies. It then presents detailed case studies from around the world with extensive illustrations, supplying a wider, global-scale picture of wetlands geomorphology and biodiversity. The final chapters discuss some unique applications of coastal wetlands, including geological monitoring, uses in biotechnology and agriculture, and various experimental mesocosms. This is ideal as supplementary reading to support students on a wide range of earth and life science courses, from environmental science, ecology and palaeoecology to geomorphology and geography. It will also be a valuable interdisciplinary reference for researchers.
Title from publisher's bibliographic system (viewed on 08 Oct 2015).
Keywords: Wetland ecology; Wetland conservation; Coasts; Coastal ecology